STRATEGI KOMUNIKASI BADAN AMIL ZAKAT NASIONAL KOTA PALOPO DALAM PENGUMPULAN ZAKAT - Aslam, Muhammad; Masmuddin, Masmuddin; Mahmud, Adilah (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2025)
This research aims 1) To understand and analyze the communication strategy of BAZNAS Palopo in collecting zakat; 2) To understand and analyze the effectiveness of BAZNAS Palopo communication strategy in collecting zakat; 3) To analyze the constraints/obstacles faced by BAZNAS Palopo in collecting zakat. This research is qualitative research with a communication approach. The subjects in this research were five BAZNAS Commissioners in Palopo. The research results show that the strategies used by BAZNAS Palopo in collecting zakat are formulating strategies, implementing strategies and evaluating strategies; To ensure that BAZNAS Palopo communication plan is successful in collecting zakat, BAZNAS Palopo is conducting (1) Intensive Socialization and Education, (2) Utilizing Social Media and Digital, (3) Collaboration with Islamic Institutions and Mosques, (4) Payments for Zakat Are Easy to Access, (5) Personalized Ads and Marketing, (6) Openness and Regular Reporting, (7) Engagement of Religious and Community Leaders, (8) Outstanding assistance; The following are the challenges/barriers that BAZNAS Palopo faces when collecting zakat: the general public's ignorance of the zakat obligation, distrust towards zakat management organizations, insufficient technology and infrastructure to process zakat payments, rivalry with other organizations that collect zakat, Socialization and communication are not the best, direct-giving culture, Additionally, the majority of Palopo residents still view BAZNAS Palopo as a part of the Palopo regional administration, making it difficult for those who are less supportive of the Palopo government to make zakat payments at BAZNAS.